Reliability and validity of the Finnish version of the Visual Analogue Scale Foot and Ankle (VAS-FA). Issue 6 (December 2018) - Repo, Jussi P.; Tukiainen, Erkki J.; Roine, Risto P.; Kautiainen, Hannu; Lindahl, Jan; Ilves, Outi; Järvenpää, Salme; Häkkinen, Arja
Highlights: Assessing patient-centered outcomes is essential to capture treatment effectiveness. No validated foot and ankle-specific PROM has been available in Finnish. The VAS-FA was translated and adapted into Finnish. Validity and reliability of the Finnish version of the VAS-FA were good. Abstract: Background: There have previously been no validated foot and ankle-specific patient-reported outcome measures in Finnish. Methods: The Visual Analogue Scale Foot and Ankle (VAS-FA) was translated and adapted into Finnish. Thereafter, 165 patients who had undergone foot and ankle surgery completed a questionnaire set on two separate occasions. Analyses included testing of floor-ceiling effect, internal consistency, reproducibility, and validity. Results: Minor linguistic differences emerged during the translation. Some structural adjustments were made. The mean (SD) total VAS-FA score was 74 (23). In the three subscales, maximum scores were noted in 2–5% of the responses, and internal consistency ranged from 0.81 to 0.94. Reproducibility was excellent (ICC, 0.97). The total VAS-FA score correlated significantly with the Lower Extremity Functional Scale ( r  = 0.84) and the 15D Mobility dimension ( r  = 0.79). The VAS-FA loaded on two factors (pain/movement and problems/limitations). Conclusions: The Finnish version of the VAS-FA has high reliability and strong validity.